2011
DOI: 10.1038/bjc.2011.185
|View full text |Cite
|
Sign up to set email alerts
|

End-of-study safety, immunogenicity, and efficacy of quadrivalent HPV (types 6, 11, 16, 18) recombinant vaccine in adult women 24–45 years of age

Abstract: Background:Previous analyses from a randomised trial in women aged 24–45 years have shown the quadrivalent human papillomavirus (qHPV) vaccine to be efficacious in the prevention of infection, cervical intraepithelial neoplasia (CIN), and external genital lesions (EGLs) related to HPV 6/11/16/18. In this report, we present end-of-study efficacy, safety, and immunogenicity data with a median follow-up time of 4.0 years.Methods:We enrolled 3819 24–45-year-old women with no history of cervical disease or genital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
216
0
26

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 305 publications
(248 citation statements)
references
References 23 publications
6
216
0
26
Order By: Relevance
“…Consequently, we did not include the need for vaccine booster shots in our model. The protective effect of vaccines is known to last at least several years and the need for boosters is currently unknown (Paavonen et al, 2009;Castellsague et al, 2011). Using deterministic modeling, our model took into account the "herd immunity" effect corresponding to a decrease in HPV 16/18 infections and anal cancers in non-vaccinated subpopulations of females due to vaccination coverage of other individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, we did not include the need for vaccine booster shots in our model. The protective effect of vaccines is known to last at least several years and the need for boosters is currently unknown (Paavonen et al, 2009;Castellsague et al, 2011). Using deterministic modeling, our model took into account the "herd immunity" effect corresponding to a decrease in HPV 16/18 infections and anal cancers in non-vaccinated subpopulations of females due to vaccination coverage of other individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In the basecase, we considered a high efficacy as observed in clinical trials which conducted statistical analyses in "per protocol" cohorts. The efficacy of vaccines in girls and young women who have never been infected with HPV is close to 100%, whereas efficacy drops significantly in "intention to treat" analyses (full cohort) (Rambout et al, 2007;Paavonen et al, 2009;Munoz et al, 2010;Castellsague et al, 2011). We therefore considered HPV vaccination with different levels of efficacy in sensitivity analyses.…”
Section: Ribassin-majed Et Al 147mentioning
confidence: 99%
“…Já a vacina tetravalente apresenta VLP de HPV dos tipos 6, 11, 16 e 18, conferindo proteção à infecção e lesões citadas acima, assim como prevenção de verrugas genitais e lesões vulvares e vaginais (CUTTS et al, 2007;JOSÉ, 2008). Castellsagué et al (2011) demonstraram que a vacina tetravalente dos sorotipo, 6, 11, 16 e 18 recombinante apresentou imunogenicidade e eficácia em mulheres com 24 a 45 anos de idade.…”
Section: Vacinas Profiláticas Contra a Infecção Por Hpvunclassified
“…37 The end-of-study results of a phase III efficacy, safety, and immunogenicity study involving the quadrivalent vaccine in women aged 24-45 y reported a vaccine efficacy against disease or infection related to HPV 6,11,16, and 18 in the accordingto-protocol (ATP) population of 88.7% (95% CI: 78.1, 94.8), and 66.9% (95% CI: 4.3, 90.6) in the intention-to-treat population (ITT), i.e., women who were seropositive and DNA negative for the HPV vaccine type at the time of enrolment, who received at least one dose of the vaccine. 38 In the intermediate analysis of this study, Munoz et al 39 reported a 30.9% (95% CI 11.1-46.5) efficacy of the quadrivalent vaccine against disease or infection related to HPV 6/11/16/18 in the ITT population, here including women aged 24-45 y with infection or disease present at baseline. This low percentage, with reference to the 90.5% (95% CI 73.7-97.5) efficacy observed in the ATP population, confirms that HPV vaccines are most effective when administered before exposure to HPV because they have no therapeutic effect and can only protect against HPV types not already acquired at the time of vaccination.…”
Section: Human Papillomavirus (Hpv) Vaccinationmentioning
confidence: 99%